The Historical Development of Saung Budaya Sumedang: Center for Arts and Culture in Jatinangor (2000–2023) - Amalia, Lenny Salsha; Permana, Agus; Purnama, Agung (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
The Saung Budaya Sumedang (Sabusu) has played a pivotal role as a center for arts and culture in Jatinangor, Sumedang Regency, since its establishment in 2000. This study aims to examine the historical development of Sabusu, analyzing its contributions to preserving local arts and culture amidst evolving social dynamics from 2000 to 2023. Employing historical research methods encompassing heuristics, source criticism, interpretation, and historiography, the study draws on primary and secondary data, including interviews, videos, and related academic literature. Results indicate that Sabusu has undergone significant transformations, including name changes and shifts in management. Initially a hub for traditional arts, Sabusu faced challenges due to privatization and commercialization, leading to diminished cultural activities. However, since 2019, revitalization efforts by the Ibu Djati Foundation have restored its role as a cultural and educational space. Despite facing modern challenges such as globalization and shifting youth interests, Sabusu continues to adapt by organizing traditional art programs and fostering community engagement. This study underscores the importance of Sabusu as a model for cultural preservation and its potential to inspire similar initiatives in Indonesia.